A note on the species occurrence, distributional ecology and fisheries interactions of cetaceans in the Mergui (Myeik) Archipelago, Myanmar - Smith, Brain D.; Tun, Mya Than (J. Cetacean Res. Manage., 2023)
A vessel-based line-transect survey for cetaceans conducted during 23 February-6 March 2005 of the nearshore waters (to a depth of 40- 60m) of the Mergui (Myeik) Archipelago of southern Myanmar searched along 955km of trackline resulting in 30 cetacean sightings. These included Indo-Pacific bottlenose dolphins Tursiops aduncus (n=15), Indo-Pacific humpback dolphins Sousa chinensis (n=3), spinner dolphins Stenella longirostris (n=4; the largest of these was mixed with pantropical spotted dolphins Stenella attenuata), Irrawaddy dolphins Orcaella brevirostris (n=1), finless porpoises Neophocaena phocaenoides (n=1), Bryde’s whales Balaenoptera edeni/brydei (identification tentative; n=1), one unidentified baleen whale (probably also a Bryde’s whale) and four unidentified delphinid groups. Irrawaddy dolphins and finless porpoises were found in shallow, brackish waters, Indo-Pacific humpback dolphins also in shallow waters but those less affected by freshwater inputs and Bryde’s whales and Indo-Pacific bottlenose, spinner and spotted dolphins in deeper and clearer waters. In total 2,565 gill netters/long liners (95% CI=1,228-3,903), 1,301 squid jiggers (95% CI=611-1,992) and 532 stern trawlers (95% CI=154-910) were estimated to be operating in the study area. Concentrations of gill netters/long liners were particularly high in shallow nearshore waters and at least 150 were operating in the bay where the only sightings of Irrawaddy dolphins and finless porpoises were made. There is a need to better assess nearshore cetacean populations, investigate whether or not incidental and intentional catches are sustainable and incorporate a cetacean element into an initiative to establish a marine protected area network in the Mergui Archipelago.